2016
DOI: 10.1016/j.colsurfa.2016.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced visible-light-driven photocatalytic performance of mesoporous W-Ti-SBA-15 prepared through a facile hydrothermal route

Abstract: h i g h l i g h t s• A series of tungsten-titaniumcocontained SBA15 composites were fabricated by a simple synthetic route.• These samples showed enhanced catalytic performance in comparison to those comprising bare tungsten or titanium component.• The enhancement of photocatalytic behavior under visible-light irradiation was discussed. t r a c tA facile and one-step hydrothermal procedure was adopted to fabricate a series of W-Ti-SBA15 composites (WTS). These as-prepared composites were systematically charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…The high concentration of Ti formed a different framework from that of the incorporated silica species. 43 Thereafter, the decreased number of Si sites around the P123 surfactant and the shorter hydrolysis time of Ti resulted in a three-dimensional porous structure after the condensation process. 27 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The high concentration of Ti formed a different framework from that of the incorporated silica species. 43 Thereafter, the decreased number of Si sites around the P123 surfactant and the shorter hydrolysis time of Ti resulted in a three-dimensional porous structure after the condensation process. 27 …”
Section: Resultsmentioning
confidence: 99%
“…The Ti2p 3/2 or Ti2p 1/2 peak shied to a lower binding energy by approximately 2 eV compared to the anatase phase of Ti 4+ . 32, 43 Gao et al 48 indicated that the blueshi might be associated with the Ti-O-Si bonds, resulting in a more positive charge on Ti, a less negative charge on O, and more negative charge on Si. With increasing Ti content, the intensity of the peak increased as the Ti/Si ratio improved.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, the synthesis and photocatalytic assessment of mesoporous W-Ti-SBA15 composites were investigated, and these heterojunction-structured composites showed enhanced photocatalytic efficiency in comparison to single-component samples [29]. However, the photocatalytic performance was not as that good as we had expected, mainly attributing to the serious aggregation of TiO 2 particles since the excess amount of titanium precursor was added during synthesis.…”
Section: Introductionmentioning
confidence: 90%
“…The synthetic procedure was similar to the previous study except that the amount of titanium and tungsten precursors was greatly reduced [29]. A series of W-Ti-SBA15 mesoporous composites were prepared and nominated as 5%WTSx, where 5% and x were defined as theoretical mass ratios of formed WO 3 /TiO 2 and TiO 2 /SiO 2 , respectively.…”
Section: Synthesis Of W-ti-sba15 Compositesmentioning
confidence: 99%